(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pulpitis is a pressing issue in pediatric dentistry, significantly affecting a child’s overall health and quality of life. Dental diseases that begin at an early age not only cause pain and discomfort but also negatively impact nutrition, speech development, and psycho-emotional well-being. Therefore, the prevention of pulpitis in children holds great importance in dentistry.